NEW PERMIAN BRACHIOPODS OF THE ORDER TEREBRATULIDA FROM THE SOUTHWESTERN DARVAZ (NORTHERN PAMIRS): 3. SUPERFAMILY LOBOIDOTHYROIDEA - Smirnova T.N.; Grunt T.A. (My University, 2003)
Three new species and one new genus of Terebratulida belonging to the superfamily Loboidothyroidea are described from the Permian of the southwestern Darvaz (Tajikistan). The terebratulid assemblage from the Permian of this region is generally represented by 16 species, including 12 new species. These species belong to six genera, including three new genera, four families, and four superfamilies. The biostratigraphic distribution and biogeographic features of this highly endemic brachiopod assemblage are analyzed.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская